Steel and die

CN117904542BActive Publication Date: 2026-10-27DAIDO STEEL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311327376.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-10-19
Filing Date
2023-10-13
Publication Date
2026-10-27
Estimated Expiration
2043-10-13

AI Technical Summary

Technical Problem

[0013]然而,制造满足全部的上述3种特性的钢材并不容易

Benefits of technology

[0036]此外,“可切削性”和“耐热裂解性”通常是元素的影响相反的特性。在这些当中,对于供于PH工序的钢材,与耐热裂解性相比,更重视可切削性。由于本发明涉及的钢材对Si量进行了优化,因此能够在不显著降低耐热裂解性的情况下提高可切削性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117904542B_ABST
    Figure CN117904542B_ABST
Patent Text Reader

Abstract

The present invention relates to a steel material containing: 0.19 ≤ C ≤ 0.31 mass%, 0.010 ≤ V ≤ 0.180 mass%, Mn ≤ 1.50 mass%, 5.60 ≤ Cr ≤ 6.60 mass%, Cu + Ni ≤ 0.84 mass%, 0.60 ≤ Si ≤ 1.40 mass%, 0.60 ≤ Mo ≤ 2.00 mass%, 0.001 ≤ Al ≤ 0.080 mass%, and 0.003 ≤ N ≤ 0.040 mass%, with the balance consisting of Fe and unavoidable impurities, and the contents of Mn and Cr satisfy Mn / Cr > 0.150.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to steel and molds, and more specifically, to steel suitable for manufacturing molds of large mass and size, and to molds using the steel. Background Technology

[0002] Because molds are subjected to repeated stress and heat during use, the steel used for molds must possess excellent properties such as hardness, impact resistance, thermal cracking resistance, and wear resistance. Therefore, various solutions have been proposed for steels with such properties.

[0003] For example, Patent Document 1 discloses a hot tool steel containing predetermined amounts of C, Si, Mn, Cr, Mo, and V, with the balance consisting of Fe and unavoidable impurities.

[0004] The document states the following two points: (A) When the Si content is 0.01% by mass or more and less than 0.25% by mass, a hot tool steel with machinability and thermal conductivity higher than that of general-purpose mold steel (e.g., JIS SKD61) can be obtained; and (B) When the Mn, Cr, Mo, and V contents are optimized, a hot tool steel with high hardenability and high impact value can be obtained.

[0005] The mold manufacturing process typically includes: (a) a first step of manufacturing steel suitable for mold making; and (b) a second step of manufacturing the mold from the obtained steel.

[0006] The first process (manufacturing of steel for molds) includes various steps. The main steps are melting, refining, casting, homogenization heat treatment, hot working, normalizing, tempering, and spheroidizing annealing. Sometimes, more than one of the normalizing, tempering, and spheroidizing annealing steps is omitted.

[0007] The second process (the process of making molds from steel) has the following two steps.

[0008] The first type of process is the HT process. The HT process typically includes: (a) machining (rough machining) the spheroidized annealed steel into a rough mold shape; (b) quenching (H) and tempering (T) the rough-machined mold; (c) fine machining the quenched and tempered mold; and (d) surface modification of the fine-machined mold as needed.

[0009] The second type of process is the PH process. The PH process typically includes: (a) quenching and tempering the steel (not necessarily spheroidized annealed steel) to a suitable hardness; (b) machining (finishing) the tempered steel; and (c) surface modification of the machined mold as needed.

[0010] For example, in the case of die-casting molds, the HT process is mostly used for manufacturing, but when the required hardness of the mold is low, the PH process is sometimes used.

[0011] The required characteristics of steel supplied for the PH process and molds manufactured using the PH process are: (1) good machinability, (2) high impact value at low quenching speed, and (3) small hardness difference between the surface and the center (hardness homogeneity).

[0012] In addition, in order to obtain a high impact value even at a low quenching rate, the following three factors need to be met: (a) fewer large foreign objects, (b) fewer carbides or carbonitrides distributed in a dotted pattern, and (c) high hardenability.

[0013] However, it is not easy to manufacture steel that meets all three of the above characteristics.

[0014] [Patent Document 1] Japanese Patent Application Publication No. 2011-001572 Summary of the Invention

[0015] The problem to be solved by the present invention is to provide steel suitable for the PH process, namely steel with good machinability, impact value and hardness homogeneity.

[0016] In addition, another problem that the present invention aims to solve is to provide steel that has good machinability, impact value and hardness homogeneity even when the mass and size of the steel are large.

[0017] Furthermore, another problem that the present invention aims to solve is to provide a mold made of such steel.

[0018] The steel involved in this invention for solving the above-mentioned problems contains:

[0019] 0.19≤C≤0.31% by mass

[0020] 0.010≤V≤0.180% by mass

[0021] Mn≤1.50% by mass

[0022] 5.60≤Cr≤6.60% by mass

[0023] Cu+Ni≤0.84% ​​by mass

[0024] 0.40≤Si≤1.40% by mass

[0025] 0.60≤Mo≤2.00% by mass

[0026] 0.001≤Al≤0.080% by mass, and

[0027] 0.003 ≤ N ≤ 0.040% by mass, the balance being Fe and unavoidable impurities, and the contents of Mn and Cr satisfy Mn / Cr > 0.150.

[0028] The steel involved in this invention

[0029] The weight is over 3000kg.

[0030] Among the longitudinal dimension (L1), the transverse dimension (L2), and the height dimension (L3), the smallest dimension (L) is... min The preferred diameter is 300mm or more.

[0031] In addition, the hardness of the central part of the steel involved in this invention is preferably 35HRC or higher and 45HRC or lower.

[0032] Furthermore, the molds involved in this invention are made of the steel involved in this invention and are composed of steel with a mass of 2000 kg or more.

[0033] The steel involved in this invention has two main characteristics. The first characteristic is that the carbon (C) and v (V) content is relatively low. This suppresses the decrease in impact value caused by coarse foreign matter and dotted carbides or carbonitrides. On the other hand, when the C and V content is low, the austenite grains tend to coarsen during quenching. However, even with low C and V content, the decrease in impact value caused by the coarsening of austenite grains during quenching can be suppressed by adding appropriate amounts of Al and N and adjusting the quenching conditions.

[0034] The second major feature is that by introducing parameters such as "Mn / Cr" while specifying the Cr and Mn amounts separately, the optimal range for Mn and Cr amounts was discovered. When the Mn and Cr amounts are optimized, the decrease in impact value caused by the reduction in hardenability is suppressed, and the homogeneity of hardness is improved.

[0035] In particular, "spheroidizing annealing (SA) property" and "hardenability," as well as "hardenability" and "hardness homogeneity," are characteristics with opposite effects from the elements. Among these, steel supplied for the PH process does not necessarily require SA property. Because the steel involved in this invention has optimized Cr and Mn content, it is possible to balance hardenability and hardness homogeneity.

[0036] Furthermore, "machinability" and "thermal decomposition resistance" are generally properties with opposite effects from elements. Among these, for steels supplied for the PH process, machinability is more important than thermal decomposition resistance. Since the steel of this invention has optimized Si content, machinability can be improved without significantly reducing thermal decomposition resistance. Attached Figure Description

[0037] Figure 1 This is a graph showing the relationship between C and the impact value.

[0038] Figure 2 This is a graph showing the relationship between V quantity and impact value.

[0039] Figure 3 This is a graph showing the ranges of C and V.

[0040] Figure 4 This is a graph showing the effect of Mn and Cr content on the impact value when the quenching rate is low.

[0041] Figure 5 This is a graph showing the effect of Cr on softening resistance.

[0042] Figure 6 This is a graph showing the range of Mn and Cr amounts.

[0043] Figure 7 This is a graph showing the effect of Si content on machinability.

[0044] Figure 8 This is a graph showing the effect of Mo on softening resistance.

[0045] Figure 9 This is a schematic diagram used to illustrate the cut position of the test piece. Detailed Implementation

[0046] The following is a detailed description of one embodiment of the present invention.

[0047] [1. Steel]

[0048] [1.1. Composition]

[0049] [1.1.1. Main Constituent Elements]

[0050] The steel involved in this invention contains the following elements, with the balance consisting of Fe and unavoidable impurities. The types of added elements, their composition ranges, and the reasons for their limitation are described below.

[0051] (1) 0.19 ≤ C ≤ 0.31 wt%

[0052] Fine particles (carbides, carbonitrides) with a diameter of less than 0.5 μm function as "pinning particles" to inhibit austenite grain growth during quenching. When the carbon content is too low, the amount of pinning particles is insufficient during quenching. As a result, grain coarsening occurs, and steel properties such as impact resistance, fracture toughness, and ductility may deteriorate.

[0053] Furthermore, when the amount of carbon is too low, the martensitic transformation initiation temperature (Ms point) becomes too high. As a result, hardenability increases, but the impact value may decrease.

[0054] Furthermore, when the amount of carbon is too small, it is difficult to obtain a hardness of 35 HRC or higher (preferably 36 HRC or higher) by tempering at 560–600°C.

[0055] Therefore, the amount of C needs to be 0.19% by mass or more. The amount of C is preferably 0.20% by mass or more, and more preferably 0.21% by mass or more.

[0056] On the other hand, when carbon content is excessive, coarse carbides or carbonitrides may crystallize during casting. These become "foreign objects" that reduce impact strength. It is difficult to dissolve and eliminate these coarse foreign objects through heat treatment (homogenization heat treatment, normalizing). Even after quenching and tempering, these coarse foreign objects may remain undissolved, sometimes observed in diameters exceeding 3 μm. These undissolved and remaining foreign objects become the starting point of failure, contributing to reduced impact strength and fatigue strength.

[0057] Furthermore, when ingots are hot-worked into block or rod-shaped steel, slow cooling rates after hot working can sometimes cause carbides or carbonitrides to precipitate in a dotted pattern, resulting in a decrease in impact value. This phenomenon becomes more pronounced when there is an excess of carbon.

[0058] Therefore, the amount of C needs to be 0.31% by mass or less. The amount of C is preferably 0.30% by mass or less, and more preferably 0.29% by mass or less.

[0059] (2) 0.010 ≤ V ≤ 0.180 mass %

[0060] V combines with C and / or N in steel to form carbides, carbonitrides, and / or nitrides. These all function as pinning particles. Therefore, when the amount of V is too low, the amount of pinning particles is insufficient during quenching.

[0061] Furthermore, when the amount of V is too small, the degree of secondary hardening during tempering is reduced. As a result, it is difficult to obtain a hardness of 35 HRC or higher (preferably 36 HRC or higher) when tempering at 560–600 °C.

[0062] Therefore, the V content needs to be 0.010% by mass or more. The V content is preferably 0.013% by mass or more, and more preferably 0.016% by mass or more.

[0063] On the other hand, when V is in excess, coarse foreign matter and / or dotted carbides or carbonitrides increase. As a result, the decrease in impact value may become more pronounced. Furthermore, when V is in excess, the cost of steel increases, which contradicts the goal of resource conservation.

[0064] Therefore, the V content needs to be 0.180% by mass or less. The V content is preferably 0.170% by mass or less, more preferably 0.160% by mass or less.

[0065] (3) Mn / Cr > 0.150:

[0066] The mass ratio of Mn to Cr in steel (Mn / Cr) affects spheroidizing annealing (SA) properties. Generally, the lower the Mn / Cr ratio, the higher the SA properties. Therefore, in the case of steel supplied for the HT process, it is preferable to reduce the Mn / Cr ratio to ensure high SA properties and sufficient softening using easy SA. However, in order to keep the Mn / Cr ratio low, Mn cannot be increased, thus limiting the improvement of hardenability.

[0067] In contrast, hardenability is less important for steel supplied for the PH process. On the other hand, hardenability is very important when dealing with large steel pieces or molds in the PH process.

[0068] To achieve high hardenability, the Mn / Cr ratio needs to exceed 0.150. Preferably, the Mn / Cr ratio is 0.155 or higher, and more preferably 0.160 or higher.

[0069] (4) Mn≤1.50% by mass:

[0070] Mn affects hardenability. Generally, the higher the Mn content, the higher the hardenability. However, when the Mn content is excessive, the thermal conductivity decreases, and the resistance to thermal cracking deteriorates. Additionally, when the Mn content is excessive, the amount of retained austenite increases. Retained austenite sometimes decomposes during tempering, but regardless of whether it decomposes or not, retained austenite can adversely affect the properties of the steel. Therefore, the Mn content needs to be 1.50% by mass or less. Preferably, the Mn content is 1.45% by mass or less, more preferably 1.40% by mass or less.

[0071] (5) 5.60 ≤ Cr ≤ 6.60 wt%

[0072] Cr affects hardenability, hardness homogeneity, and high-temperature strength. When the Cr content is too low, hardenability and hardness homogeneity decrease. Additionally, high-temperature strength also decreases. Therefore, the Cr content needs to be 5.60% by mass or more. Preferably, the Cr content is 5.70% by mass or more, and more preferably 5.80% by mass or more.

[0073] On the other hand, when the Cr content is excessive, the resistance to softening decreases. That is, the mold surface, which is in contact with the molten metal during use, becomes very hot, but the mold surface heated to this temperature is prone to softening. When the high-temperature strength decreases due to softening, the resistance to thermal cracking also deteriorates. In addition, softening becomes significant in areas exceeding the maximum hardness, making it difficult to adjust the tempering hardness. This is because hardness is sensitive to changes in furnace temperature.

[0074] Furthermore, when the Cr content is excessive, the thermal conductivity decreases. As a result, thermal stress increases, and resistance to thermal decomposition deteriorates. Additionally, when the Cr content is excessive, Cr-based carbides precipitate at grain boundaries after hot working, thus contributing to a decrease in impact value. Moreover, when the Si content is below 0.50% by mass, increasing the Cr content significantly reduces machinability.

[0075] Therefore, the Cr content needs to be 6.60% by mass or less. The Cr content is preferably 6.50% by mass or less, more preferably 6.40% by mass or less.

[0076] (6) Cu + Ni ≤ 0.84% ​​by mass:

[0077] In this invention, as described above, hardenability and resistance to softening are ensured through a balance of Cr and Mn (Cr amount, Mn amount, Mn / Cr ratio). In contrast, both Cu and Ni have the effect of improving hardenability and resistance to softening, but their effects are not significant. Conversely, when the amount of Cu+Ni is excessive, the adverse effects described later become significant. Therefore, Cu and Ni are specified by their total amounts, and these total amounts are defined as having an upper limit that minimizes their impact on hardenability.

[0078] As an indicator of the effectiveness of alloying elements in improving the hardenability of steel, there is a "hardenability characteristic value." A higher hardenability characteristic value indicates a greater improvement in hardenability. The hardenability characteristic value is determined by the type and amount of alloying element. The hardenability of steels with different compositions is evaluated by summing the hardenability characteristic values ​​corresponding to the type and amount of alloying element.

[0079] Here, the hardenability characteristic value is 0.125 when 0.10 wt% Mn is added. On the other hand, the hardenability characteristic value is 0.062 when 0.42 wt% Ni is added, and the hardenability characteristic value is also 0.062 when 0.42 wt% Cu is added. That is, the hardenability characteristic value (summated) when 0.42 wt% Cu and Ni are added respectively (totaling 0.84 wt%) is 0.124. This value is approximately equal to the hardenability characteristic value (=0.125) when 0.10 wt% Mn is added. This means that when the Cu+Ni content is below 0.84 wt%, the effect on improving hardenability is small. When the Cu+Ni content is around 0.84 wt%, the effect on improving high-temperature strength is also small.

[0080] On the other hand, when the Cu+Ni content exceeds 0.84% ​​by mass, various adverse effects emerge. Specifically, these include increased susceptibility to cracking during hot working, increased retained austenite, decreased thermal conductivity, and increased costs. Therefore, the Cu+Ni content needs to be below 0.84% ​​by mass. In this invention, since the condition of Mn / Cr > 0.150 needs to be met, the total amount of Mn and Cr, which contributes to improving hardenability, exceeds 6.44% by mass (see reference). Figure 6 Therefore, if the Cu+Ni content is below 0.84% ​​by mass, it has little effect on hardenability. The Cu+Ni content is preferably below 0.78% by mass, and more preferably below 0.72% by mass.

[0081] (7) 0.40 ≤ Si ≤ 1.40 wt%

[0082] When the Si content is too low, machinability decreases, making it difficult to reliably machine large molds industrially. In particular, for the steel of this invention, since the manufacture of large molds is envisioned, the amount of cutting is also high, requiring good machinability. Therefore, the Si content needs to be 0.40% by mass or more. Preferably, the Si content is 0.45% by mass or more, more preferably 0.50% by mass or more.

[0083] On the other hand, when the amounts of C, V, and N are relatively high, and the amount of Si is excessive, there may be more coarse crystals and / or carbides or carbonitrides distributed in a dotted pattern.

[0084] Furthermore, compared to high resistance to thermal decomposition, good machinability is more important for steel supplied for the PH process. However, when the Si content is excessive, the thermal conductivity decreases. As a result, the thermal stress increases when used as a die-casting mold, and the resistance to thermal decomposition may deteriorate. When the resistance to thermal decomposition is excessively reduced, it becomes difficult to use as a die-casting mold. Therefore, the Si content needs to be 1.40% by mass or less. The Si content is preferably 1.30% by mass or less, and more preferably 1.20% by mass or less.

[0085] (8) 0.60 ≤ Mo ≤ 2.00 wt%

[0086] When the Mo content is too low, the degree of secondary hardening during tempering is reduced. Therefore, when the Mo content is too low, it is difficult to obtain a hardness of 35 HRC or higher (preferably 36 HRC or higher) when tempering at 560–600 °C. Furthermore, insufficient resistance to softening and high-temperature strength, and potential deterioration in thermal cracking resistance also occur. Therefore, the Mo content needs to be 0.60% by mass or higher. The Mo content is preferably 0.70% by mass or higher, and more preferably 0.80% by mass or higher.

[0087] On the other hand, excessive Mo content reduces machinability. In particular, with low Si content, excessive Mo content significantly reduces machinability. Furthermore, excessive Mo content may reduce fracture toughness. This tendency is more pronounced with high Si content. Moreover, excessive Mo content increases the cost of steel, contradicting the goal of resource conservation. Therefore, the Mo content needs to be 2.00% by mass or less. Preferably, the Mo content is 1.95% by mass or less, more preferably 1.90% by mass or less.

[0088] (9) 0.001≤Al≤0.080 mass%

[0089] The steel involved in this invention has significantly reduced carbon (C) and v (V) content compared to existing hot die steels (SKD61). Therefore, the amount of V-based carbides, carbonitrides, and nitrides that become pinned particles during quenching is less than in SKD61. Consequently, AlN particles are also used in this invention to suppress austenite grain growth.

[0090] When the Al content is too low, it is difficult to reduce oxygen during refining, leading to an increase in oxides and potentially a decrease in impact value. Furthermore, when the Al content is too low, the amount of AlN that forms pinned particles is insufficient. As a result, austenite grains coarsen during quenching heating, potentially reducing impact value, fracture toughness, and / or ductility. Therefore, the Al content needs to be 0.001% by mass or more. Preferably, the Al content is 0.002% by mass or more, and more preferably 0.003% by mass or more.

[0091] On the other hand, when the Al content is excessive, the number of coarse alumina particles increases, which may reduce the impact value and fatigue strength. In addition, the thermal conductivity decreases, and the resistance to thermal decomposition may deteriorate. Therefore, the Al content needs to be 0.080% by mass or less. The Al content is preferably 0.070% by mass or less, and more preferably 0.060% by mass or less.

[0092] It should be noted that when Ca is added to improve machinability, the amount of Al becomes very important in adapting the morphology of the compound.

[0093] (10) 0.003 ≤ N ≤ 0.040 wt%

[0094] In this invention, in order to disperse AlN particles in the austenite phase during quenching heating, the amount of N is also specified along with the amount of Al. When the amount of N is too low, the amount of AlN that acts as pinning particles is insufficient. As a result, the austenite grains coarsen during quenching heating, and the impact value, fracture toughness, and / or ductility may decrease. In addition, when the amount of N is too low, the amount of V-based carbonitrides or nitrides that act as pinning particles may also be insufficient. Therefore, the amount of N needs to be 0.003% by mass or more. The amount of N is preferably 0.004% by mass or more, and more preferably 0.005% by mass or more.

[0095] On the other hand, to add a greater amount of nitrogen than is typically adjustable in refining, specialized equipment is required for aggressive nitrogen addition, thus increasing material costs. Furthermore, when nitrogen is excessive, coarse crystals and / or dotted carbides or carbonitrides may increase. This tendency is more pronounced when C, Si, and V content are high. Additionally, excessive nitrogen leads to an overemphasis on coarse AlN, potentially reducing impact strength. Moreover, when nitrogen is excessive, nitrogen vaporization in the steel during weld repair of molds may contribute to internal or surface defects in the weld area. Therefore, the nitrogen content needs to be 0.040% by mass or less. Preferably, the nitrogen content is 0.038% by mass or less, more preferably 0.036% by mass or less.

[0096] (11) Unavoidable impurities:

[0097] The steel involved in this invention may contain unavoidable impurities. Regarding the elements that can be present as impurities in the steel involved in this invention and their contents, the following elements are included: P ≤ 0.03 wt%, S ≤ 0.006 wt%, O ≤ 0.006 wt%, W ≤ 0.30 wt%, Co ≤ 0.30 wt%, B ≤ 0.0002 wt%, Nb ≤ 0.004 wt%, Ta ≤ 0.004 wt%, Ti ≤ 0.004 wt%, Zr ≤ 0.004 wt%, Ca ≤ 0.0005 wt%, Se ≤ 0.03 wt%, Te ≤ 0.005 wt%, Bi ≤ 0.01 wt%, Pb ≤ 0.03 wt%, Mg ≤ 0.02 wt%.

[0098] In this invention, "content" refers to the "average elemental content of the steel" derived by chemical analysis methods from a predetermined mass of steel (preferably 1 gram or more per element) containing a portion of concentrated segregation, a portion of thin segregation, and a portion of average segregation, dissolved in acid.

[0099] [1.1.2. Secondary constituent elements]

[0100] In addition to the main constituent elements and unavoidable impurities mentioned above, the steel involved in this invention may further contain one or more of the following elements. The types of added elements, their composition ranges, and the reasons for their limitation are described below.

[0101] [AA group]

[0102] (12) 0.30 < W ≤ 2.00 wt%

[0103] The steel involved in this invention has lower carbon (C) and v (V) content than conventional hot die steels, and therefore sometimes lacks sufficient strength depending on the application. In such cases, adding w (W) is effective to increase strength. To achieve this effect, the w content is preferably more than 0.30% by mass. More preferably, the w content is 0.80% by mass or more.

[0104] On the other hand, when the amount of W is excessive, material costs increase. Furthermore, it can sometimes lead to deterioration of mechanical properties or increased anisotropy due to the manifestation of segregation. Therefore, the amount of W is preferably 2.00% by mass or less. More preferably, the amount of W is 1.50% by mass or less.

[0105] (13) 0.30 < Co ≤ 1.00 wt%

[0106] Like W, Co also has the effect of increasing strength. Therefore, adding Co is effective in increasing strength when it is insufficient. To achieve this effect, the amount of Co is preferably more than 0.30% by mass. More preferably, the amount of Co is 0.50% by mass or more.

[0107] On the other hand, when the amount of Co is excessive, the material cost increases. Furthermore, it can sometimes lead to a deterioration in mechanical properties or an increase in anisotropy due to the manifestation of segregation. Therefore, the amount of Co is preferably 1.00% by mass or less. More preferably, the amount of Co is 0.90% by mass or less.

[0108] It should be noted that the steel involved in this invention may contain either Co or W, or both.

[0109] [BB Group]

[0110] (14) 0.0002 < B ≤ 0.0080 wt%

[0111] When the phosphorus (P) content in steel is relatively high, P segregation at grain boundaries reduces grain boundary strength and impact value. Adding boron (B) is effective in improving grain boundary strength. However, for this to be effective, B needs to exist alone in the steel (without forming compounds). The effect of B addition disappears when B forms BN. Therefore, in N-containing steels, when adding B to improve grain boundary strength, N needs to be combined with elements other than B.

[0112] Specifically, it is preferable to combine nitride-forming elements such as Ti, Zr, and Nb, which readily form nitrides, with N. These elements are effective even at impurity levels, but if insufficient, it is preferable to add an amount exceeding the impurity level.

[0113] It should be noted that boron (BN) improves the machinability of steel. Therefore, when adding boron (B) to improve machinability, it is not necessary to actively add nitride-forming elements to the steel.

[0114] To achieve the effects described above, the amount of B is preferably more than 0.0002% by mass. More preferably, the amount of B is 0.0003% by mass or more, and even more preferably 0.0004% by mass or more.

[0115] On the other hand, even if more B is added than needed, the effect is the same, and there is no practical benefit. Furthermore, an excess of B increases the cost of steel. Therefore, the B content is preferably 0.0080% by mass or less. More preferably, it is 0.0075% by mass or less, and even more preferably 0.0070% by mass or less.

[0116] [CC Group]

[0117] (15) 0.006 < S ≤ 0.180 wt%

[0118] (16) 0.0005 < Ca ≤ 0.0500 wt%

[0119] (17) 0.03 < Se ≤ 0.50 wt%

[0120] (18) 0.005 < Te ≤ 0.100 wt%

[0121] (19) 0.01 < Bi ≤ 0.50 wt%

[0122] (20) 0.03 < Pb ≤ 0.50 wt%

[0123] In the steels involved in this invention, the addition of free-machining elements is effective in improving machinability. Specifically, free-machining elements include S, Ca, Se, Te, Bi, and Pb. The steels involved in this invention may contain any one of these free-machining elements, or may contain two or more.

[0124] To achieve sufficient machinability, the content of each machinable element is preferably greater than the aforementioned lower limit value.

[0125] On the other hand, when the content of free-machining elements is excessive, cracking is more likely to occur during hot working. Furthermore, when the content of free-machining elements is excessive, impact strength, fatigue strength, and resistance to thermal decomposition may decrease. Therefore, the content of each free-machining element is preferably below the aforementioned upper limit value.

[0126] [DD Group]

[0127] (21) 0.004 < Nb ≤ 0.100 wt%

[0128] (22) 0.004 < Ta ≤ 0.100 mass%

[0129] (23) 0.004 < Ti ≤ 0.100 wt%

[0130] (24) 0.004 < Zr ≤ 0.100 wt%

[0131] The steels involved in this invention may contain carbonitride-forming elements other than V and Al to increase the amount of carbides, carbonitrides, and / or nitrides. Specifically, Nb, Ta, Ti, and Zr are examples of carbonitride-forming elements. The steels involved in this invention may contain any one of these carbonitride-forming elements, or may contain two or more.

[0132] To suppress excessive austenite grain growth, the content of each carbonitride forming element is preferably greater than the aforementioned lower limit value.

[0133] On the other hand, when the content of carbonitride-forming elements is excessive, carbides, carbonitrides, and / or nitrides crystallize in a coarse state during casting. These coarse crystalline particles do not disappear even during homogeneous heat treatment, SA (superheating), and quenching, but remain as foreign matter, contributing to a decrease in impact value and fatigue strength. Therefore, the content of each carbonitride-forming element is preferably below the aforementioned upper limit value.

[0134] [1.2. Properties of Steel]

[0135] [1.2.1. Mass and Dimensions]

[0136] As mentioned above, the required properties for steel supplied for the PH process and for molds manufactured using the PH process are three: machinability, impact value, and hardness homogeneity. Among these three properties, the problem with large steel is the low internal impact value of large molds made from it.

[0137] The first reason for the reduced impact value in large molds is the tendency for large foreign objects to crystallize inside large steel. This is because the solidification rate during ingot manufacturing is low inside large steel.

[0138] The second reason for the reduced impact value in large molds is the slow cooling rate after hot working, which makes it easy for carbides or carbonitrides to precipitate in a dotted pattern.

[0139] The third reason for the reduced impact value in large molds is that the quenching rate is slower inside large steel.

[0140] The steel involved in this invention has low C and V content, and appropriately controlled Mn and Cr content, thus minimizing the impact of large foreign objects, slow cooling rates after hot working, and slow quenching rates. In other words, the steel involved in this invention can maintain a high degree of balance between machinability, impact resistance, and uniform hardness even when both mass and size are large.

[0141] For example, by optimizing the composition and manufacturing conditions of steel, steel with a mass of 3000 kg or more can be obtained, in addition to achieving all three of the aforementioned properties at a practical level. With further optimization of the composition and manufacturing conditions, steel with a mass of 4000 kg or more, or even 5000 kg or more, can be manufactured.

[0142] Furthermore, when the composition and manufacturing conditions of the steel are minimized, the smallest dimension (L1) among the longitudinal dimension (L1), transverse dimension (L2), and height dimension (L3) can be obtained, in addition to possessing the aforementioned characteristics. min (This refers to steel with a diameter of 300mm or more.) When the composition and manufacturing conditions of the steel are further optimized, even L... min It can also be manufactured using steel with a diameter of 350mm or 400mm or more.

[0143] Here, "longitudinal dimension (L1)," "lateral dimension (L2)," and "height dimension (L3)" refer to the lengths of the three sides of the smallest cuboid circumscribed with the steel.

[0144] [1.2.2. Hardness]

[0145] [A. Definition]

[0146] In this invention, "hardness of steel" refers to (a) a test piece cut from the center (slow quenching rate area) or the outer periphery (fast quenching rate area) of a cross section of steel tempered to a predetermined hardness, and (b) the Rockwell C scale hardness measured at room temperature using the test piece.

[0147] Figure 9A schematic diagram illustrating the cutting position of the test piece is shown. For example, in the case of a block 10 of steel with dimensions a[mm]×b[mm]×c[mm] (a≤b≤c, a≥300mm), a first material 12 of a[mm]×b[mm]×d[mm] is cut from near the center along the c-axis direction. There is no particular limitation on d, but it is preferably 30 to 70mm. "Near the center" refers to the central region when the block 10 is divided into three equal parts along the c-axis direction (the direction of the maximum length of the block 10). The first material 12 is cut from any position "near the center".

[0148] Next, a second material 14, with dimensions e[mm]×f[mm]×d[mm], is cut from the center of the ab plane of the first material 12. The values ​​of e and f are preferably selected based on the size of the ab plane, the evaluation purpose, etc. For example, when a = 600-800mm and b = 900-1100mm, e = 90-120mm and f = 130-160mm are preferred.

[0149] Furthermore, a third material 16, with dimensions g[mm] × g[mm] × d[mm], is cut from the outer periphery of the first material 12. The cutting location of the third material 16 is not particularly limited, but a corner of the first material 12 is preferred. The value of g is not particularly limited, but 40 to 60 mm is preferred. Additionally, test pieces for hardness testing are cut from the second material 14 and the third material 16 respectively, and these are used to measure hardness.

[0150] That is, more specifically, “center hardness” refers to the Rockwell C scale hardness measured using a sample cut from the center of the first material 12.

[0151] "Hardening of the outer periphery" refers to the Rockwell C scale hardness measured using a non-decarburized sample cut from the outer periphery of the first material 12.

[0152] "Central part" refers to any straight line drawn radially from the center of gravity of the cut surface of the first material 12 to the outer edge of the cut surface, and the intersection point of each straight line with the outer edge of the cut surface is set as A, and the distance from the center of gravity to the intersection point A is set as R. A At that time, from the centroid of the cut surface of the first material 12 to R A / 2 area.

[0153] The “peripheral part” refers to the area located outside the central part.

[0154] [B. Heat Treatment Conditions]

[0155] The heat treatment conditions (quenching and tempering conditions) for quenched and tempered steel are not particularly limited as long as the target hardness can be achieved.

[0156] The optimal quenching temperature varies depending on the composition of the steel. Quenching temperatures are typically between 880°C and 980°C. The cooling rate during quenching varies depending on the size of the steel and the cooling method. In the case of large steel pieces, within the cooling range of 800°C to 200°C, the cooling rate at the center is usually less than 10°C / minute.

[0157] Similarly, the optimal tempering temperature varies depending on the steel's composition. Tempering temperatures are typically 560–600°C. If the desired hardness cannot be achieved through a single tempering process, repeated tempering is preferable.

[0158] [C. Hardness homogeneity]

[0159] The steel involved in this invention can achieve high hardness even when its mass and size are relatively large. Furthermore, the hardness difference between the outer periphery (where cooling is rapid) and the center (where cooling is slow) is small, indicating high hardness homogeneity.

[0160] When the composition and manufacturing conditions of the steel are optimized, the hardness (H1) of the outer periphery at room temperature is 36–44 HRC. When the composition and manufacturing conditions of the steel are further optimized, H1 is 37–43 HRC or 38–42 HRC.

[0161] When the composition and manufacturing conditions of the steel are optimized, the hardness (H2) of the center at room temperature is 35–45 HRC. When the composition and manufacturing conditions of the steel are further optimized, H2 is 36–44 HRC or 37–43 HRC.

[0162] Furthermore, when the composition and manufacturing conditions of the steel are optimized, the absolute value of the difference between H1 and H2 (ΔH=|H1-H2|) is less than 3.5HRC.

[0163] [1.2.3. Impact Value]

[0164] In this invention, "impact value of steel" refers to the impact value obtained by: (a) cutting an impact test piece from near the center of a cross-section of steel tempered to a predetermined hardness (in a region with a slow solidification rate or quenching rate), and (b) conducting an impact test at 15–35°C.

[0165] The impact test specimen is cut out near the center of the steel's cross-section. That is, from... Figure 9 The second material 14 shown is cut out as an impact test piece.

[0166] In addition, the heat treatment conditions (quenching and tempering conditions) for quenched and tempered steel are as described above, so the description is omitted.

[0167] "Impact test piece" refers to a test piece conforming to JIS Z2242:2018 (10mm×10mm×50mm, radius of curvature at the notch tip: 1mm, notch depth: 2mm, cross-sectional area of ​​the test piece at the bottom of the notch: 0.8cm²). 2 ).

[0168] Impact value (J / cm) 2 ")" refers to the absorbed energy [J] divided by the cross-sectional area (0.8 cm²) of the bottom of the notch in the test piece. 2 The value obtained is ]).

[0169] Average impact value (J / cm) 2 "" refers to the average impact value of 10 or more (preferably 10 to 20) impact test pieces.

[0170] "Low impact value rate (%)" refers to an impact value less than 20 [J / cm²]. 2 The ratio of the number of impact test pieces (n) to the total number of impact test pieces (n0) that underwent impact testing (=n×100 / n0).

[0171] In the steels involved in this invention, when the composition and manufacturing conditions are optimized, steels that exhibit high impact values ​​and small deviations in impact values ​​despite large dimensions can be obtained.

[0172] Specifically, when the composition and manufacturing conditions are optimized, an average impact value of 25 [J / cm] can be obtained. 2 Steel with an impact value of 30% or less and above.

[0173] When the composition and manufacturing conditions are further optimized, the average impact value is 26 [J / cm]. 2 ] or above 27 [J / cm 2 ]above.

[0174] Furthermore, when the composition and manufacturing conditions are further optimized, the low impact value rate is below 20% or below 10%.

[0175] [2. Mold]

[0176] The mold involved in this invention is made of the steel involved in this invention and has the following characteristics.

[0177] [2.1. Mass and Dimensions]

[0178] The steel involved in this invention exhibits excellent machinability, impact resistance, and hardness homogeneity, even when the mass and size are relatively large. Therefore, when using such steel, molds with excellent impact resistance and hardness homogeneity can be obtained even when the mass and size are relatively large.

[0179] When the composition and manufacturing conditions of the mold are optimized, a mold with a mass of 2000 kg can be obtained, in addition to achieving practical levels of impact value and hardness homogeneity. When the composition and manufacturing conditions of the mold are further optimized, molds with a mass of 3000 kg or more, or even 4000 kg or more, can be manufactured.

[0180] Furthermore, when the composition and manufacturing conditions of the mold are minimized, the smallest dimension (L') among the longitudinal dimension (L'1), transverse dimension (L'2), and height dimension (L'3) can be obtained, in addition to possessing the aforementioned characteristics. min For molds with a diameter of 250mm or more. When the mold composition and manufacturing conditions are further optimized, even L' min Molds with a diameter of 300mm or more, or 350mm or more, can also be manufactured.

[0181] Here, "longitudinal dimension (L'1)", "lateral dimension (L'2)" and "height dimension (L'3)" refer to the lengths of the three sides of the smallest cuboid that is circumscribed in the mold.

[0182] [2.2. Hardness, impact value, and hardness homogeneity]

[0183] The steel disclosed in this invention is particularly suitable for use in the PH process. Molds manufactured using the PH process have the same hardness, impact value, and hardness homogeneity as the tempered steel. Details regarding hardness, impact value, and hardness homogeneity are as described above and therefore omitted.

[0184] [3. Steel Manufacturing Methods]

[0185] The method for manufacturing steel according to the present invention includes: (a) a first step of melting raw materials mixed in a predetermined composition, refining the molten liquid, and casting the molten liquid in a mold; (b) a second step of homogenizing heat treatment of the ingot; (c) a third step of hot working the homogenized heat-treated ingot; (d) a fourth step of normalizing the hot-worked rough material as needed; (e) a fifth step of tempering the rough material as needed; (f) a sixth step of spheroidizing annealing the rough material as needed; and (g) a seventh step of quenching and tempering the rough material.

[0186] [3.1. First Process]

[0187] First, the raw materials, which are combined in a predetermined manner, are melted, the molten liquid is refined, and the molten liquid is cast in a mold (step 1). There are no particular limitations on the melting conditions, refining conditions, and casting conditions; the optimal conditions can be selected according to the purpose.

[0188] [3.2. Second Process]

[0189] Next, the ingot undergoes a homogenization heat treatment (step 2). This homogenization heat treatment is performed to thin out the component segregation that occurs during solidification and to dissolve as much of the foreign matter that crystallizes during solidification as possible, thereby homogenizing the composition. There are no particular limitations on the conditions for the homogenization heat treatment; the optimal conditions can be selected based on the desired outcome.

[0190] [3.3. Third Process]

[0191] Next, the homogenized heat-treated ingot is hot-worked (step 3). Hot working is performed to shape the ingot into a rough material with the desired shape. There are no particular limitations on the conditions for hot working; the optimal conditions can be selected according to the purpose.

[0192] [3.4. Step 4]

[0193] Next, as needed, the rough material after heat treatment is normalized (step 4). Normalizing is performed when it is necessary to homogenize and refine the microstructure of the rough material. There are no particular limitations on the normalizing conditions; the optimal conditions can be selected according to the purpose. It should be noted that the normalizing step can be omitted.

[0194] [3.5. Step 5]

[0195] Next, the rough material is tempered (step 5) as needed. Tempering is performed when it is necessary to temper the martensite or bainite produced during the cooling process after normalizing, or when carbide precipitation is required in preparation for spheroidizing annealing. There are no particular limitations on the tempering conditions; the optimal conditions can be selected according to the purpose. It should be noted that the tempering step can be omitted.

[0196] [3.6. Step 6]

[0197] Next, the rough material is spheroidized and annealed as needed (step 6).

[0198] Spheroidizing annealing is performed to obtain fine austenite grains during the quenching heating in step 7. It should be noted that the spheroidizing annealing step can be omitted.

[0199] [3.7. Step 7]

[0200] Next, the rough material undergoes quenching and tempering (step 7). Quenching and subsequent tempering are performed to temper the steel to a predetermined hardness. There are no particular restrictions on the quenching and tempering conditions, as long as the predetermined hardness can be achieved.

[0201] [4. Mold Manufacturing Method]

[0202] The molds involved in this invention include: (a) a first step of machining (finishing) steel tempered to a moderate hardness (pre-hardened (PH)); and (b) a second step of surface modification of the machined mold as needed.

[0203] There are no specific restrictions on the methods and conditions for each process; the best methods and conditions can be selected based on the objective.

[0204] [5. Function]

[0205] The required properties for steel supplied for the PH process and for molds manufactured using the PH process are: (1) machinability, (2) impact value at low quenching speed, and (3) uniformity of hardness. Hereinafter, the reasons for requiring these three properties will be explained, mainly taking die casting as an example.

[0206] [5.1. Machinability]

[0207] For steel intended for machining, it is required that even high-speed machining does not cause significant wear on machining tools. When tool wear is severe, the frequency of tool replacement increases, leading to higher machining costs. Conversely, reducing machining speed to avoid tool wear decreases machining efficiency. Therefore, for steel used in molds, it is required to be machinable at low cost and high efficiency, i.e., "good machinability."

[0208] When using the HT process to manufacture molds, the rough machining of steel softened to below 98HRB (approximately 238HV) by spheroidizing annealing does not pose a problem as it does with the PH process, even with a large amount of cutting.

[0209] In contrast, in the PH process, since a large amount of steel is cut that has been hardened to 35HRC (approximately 345HV) or higher through quenching and tempering, it is not industrially feasible for machinability to deteriorate.

[0210] On the other hand, steels with good machinability typically contain higher levels of Si, P, and / or S. Molds made from such steels generally have poor resistance to thermal decomposition. "Poor resistance to thermal decomposition" means that thermal decomposition is prone to occur and progresses easily. The reasons for this are explained below.

[0211] High-Si steel has low thermal conductivity. When a mold made of low-thermal-conductivity steel is used for die casting, the resulting thermal stress is higher due to the increased temperature fluctuation on the mold surface.

[0212] Molds made of high-P steel have low toughness. Therefore, when such molds are used for die casting, cracking becomes easy to occur and progress.

[0213] Furthermore, high-sulfur steel contains a relatively large amount of sulfides. In molds made from such steel, sulfides become the starting point or path for cracking, thus making cracking easier to occur and progress.

[0214] That is, steels containing relatively large amounts of Si, P, and / or S have good machinability. However, when such steels are used as molds, high thermal stresses are applied to the matrix. Therefore, thermal fatigue cracking, or thermal decomposition, occurs and progresses easily. In other words, "good machinability" and "good resistance to thermal decomposition" are opposites.

[0215] In contrast, the steel involved in this invention is substantially free of P and S (or optionally contains only a small amount of S), and the Si content has been optimized. Furthermore, by optimizing the composition and quenching and tempering conditions of the steel, it can be tempered to a hardness suitable for the PH process. Therefore, the steel involved in this invention exhibits good machinability without significantly compromising its resistance to thermal decomposition.

[0216] [5.2 Impact value at low quenching speed]

[0217] In the PH process, the mold is made of steel that has been tempered to a predetermined hardness. Therefore, the steel used to manufacture the mold needs not only hardness but also a high impact resistance. The reason for this is that molds with high impact resistance are less prone to developing large cracks.

[0218] To obtain a high impact value, the following three conditions must be met: (a) fewer large foreign objects, (b) fewer carbides or carbonitrides distributed in a dotted pattern, and (c) high hardenability.

[0219] [5.2.1. Few large foreign objects]

[0220] "Foreign matter" refers to substances whose composition differs from that of the matrix, such as carbides, nitrides, carbonitrides, sulfides, and oxides.

[0221] In this invention, "large foreign objects" refers to foreign objects with a size (equivalent to the diameter of a circle) of 3 μm or more.

[0222] When stress is applied to a mold, large foreign objects can easily become the starting point for cracking and the propagation path of the cracks. Therefore, to obtain a high impact value, the fewer large foreign objects, the better.

[0223] Foreign matter can be substances containing one metallic element or substances containing two or more metallic elements. Traditionally, die-casting mold steels have a high carbon (C) and v (V) content, so large foreign matter is usually composed of v-containing carbides or carbonitrides. The size and amount of v-based carbides or carbonitrides are influenced not only by the chemical composition of the steel but also by the solidification rate during casting, the temperature and time of the homogenization heat treatment, and other factors.

[0224] [5.2.2. Few carbides or carbonitrides are distributed in a dotted pattern]

[0225] When the cooling rate after hot working is low, carbides or carbonitrides precipitate at the austenite grain boundaries, depending on the composition. These carbides or carbonitrides can be rod-shaped, V-shaped, W-shaped, or wavy, with a length of 0.5–3 μm in the longest measuring direction. Although smaller than the aforementioned "coarse foreign matter," these carbides or carbonitrides are discontinuously continuous at the grain boundaries, exhibiting a dotted distribution. Therefore, the presence of such carbides or carbonitrides easily leads to grain boundary damage, significantly reducing the impact value.

[0226] [5.2.3. High hardenability]

[0227] As steel increases in size, the cooling rate during quenching decreases. This tendency is particularly pronounced within the steel. Therefore, in the case of mold manufacturing using the PH process, the internal cooling rate during quenching decreases as steel has become larger with the increasing size of molds in recent years. Consequently, the reduction in the impact value of molds cut from large steel in the PH process becomes a problem.

[0228] [5.2.4. High Impact Value]

[0229] Based on the above reasons, there is a strong demand for steel that can achieve high impact values ​​even at low quenching rates, i.e., "steel with good hardenability." In other words, "good hardenability" means that coarse bainite will not be generated even at low quenching rates.

[0230] On the other hand, steels with good hardenability have poor ferrite (SA) properties. This is because such steels are difficult to precipitate carbides during slow cooling (SA), and the ferrite phase transformation is also difficult to carry out, thus making it difficult to obtain SA texture (texture obtained by carbides being dispersed in the parent phase of ferrite).

[0231] In contrast, steel supplied for the PH process does not necessarily need to consider hardenability (SA). However, spheroidizing annealing is sometimes performed to obtain fine austenite grains during the subsequent quenching heating. The steel involved in this invention has optimized Cr and Mn content to suit such a PH process, thus exhibiting good hardenability.

[0232] [5.3. Hardness Homogeneity]

[0233] To temper steel to a predetermined hardness (35–45 HRC), quenching and tempering are performed. When quenching large steel sections, the quenching rates differ between the surface and interior sides. Consequently, the ratios of phases such as martensite, bainite, and retained austenite sometimes differ between the surface and interior sides. When tempered in this state, the hardness of the surface and interior sides becomes different.

[0234] Furthermore, when molds are made from such steel (by machining), the hardness of the cut mold surface (the inner side of the PH steel) differs from the hardness of the steel surface because the interior of the steel is exposed as the surface of the mold.

[0235] Hardness difference is a difference in steel properties. As mentioned above, the hardness difference between the surface and interior sides of PH steel is an important factor in ensuring mold performance. A smaller hardness difference between the surface and interior sides is preferred, and this state is evaluated as "good hardness homogeneity." In this invention, good hardness homogeneity is exhibited due to the optimization of Cr and Mn content.

[0236] [5.4. Resistance to softening]

[0237] The surface of a die-casting mold heats up due to contact with the molten metal. As the number of shot blasting passes increases, the cumulative exposure time to high temperatures also increases, thus reducing the hardness of the mold surface. This softening leads to reduced high-temperature strength, resulting in deterioration of heat resistance and cracking resistance.

[0238] Based on the above reasons, in addition to the three characteristics mentioned above, die-casting molds also require resistance to softening, i.e., "high resistance to softening." However, it should be noted that steels with improved softening resistance through low-Cr content have low high-temperature strength. This is because low-Cr steel lacks solid solution strengthening at high temperatures. The decrease in high-temperature strength deteriorates its resistance to thermal cracking. In other words, "good resistance to softening" and "good resistance to thermal cracking" are opposites.

[0239] In contrast, the steel involved in this invention has optimized Cr and Mn content. Therefore, the steel involved in this invention exhibits good resistance to softening without significantly impairing hardenability and resistance to thermal cracking.

[0240] Example

[0241] [1. Verification experiment on the optimal element amount]

[0242] [1.1. Summary]

[0243] The following again illustrates the items that should be achieved in this invention.

[0244] (1) Machinability

[0245] (2) Impact value at low quenching speed

[0246] (a) Few large foreign objects

[0247] (b) Carbides or carbonitrides distributed in a dotted pattern (hereinafter collectively referred to as "grain boundary carbides") are few.

[0248] (c) High hardenability

[0249] (3) Hardness homogeneity

[0250] In the following verification experiment, objects other than (2)(a) will be used as objects. There are three reasons for this.

[0251] The first reason is that (2)(a) can only be accurately verified using steel made from industrial-sized ingots with a low solidification rate (mass of 8 tons or more).

[0252] The second reason is that when using ingots of 8 tons or more to manufacture large steel products, the cost and investigation time are too high.

[0253] The third reason is that the influence of (2)(a) is very large, so in order to accurately verify the influence of (2)(b) or (2)(c) on the impact value, the influence of (2)(a) should be excluded.

[0254] Therefore, steel with a small cross-section (diameter: 82mm × length: approximately 3000mm) was manufactured from ingots with a high solidification rate (small ingots with a mass of 150kg). Next, test pieces made from this steel were subjected to heat treatment simulating industrial manufacturing methods (i.e., steel for large molds and methods for manufacturing large molds). Based on this, it was considered that the properties of this steel "other than (2)(a)" in the manufacture of molds from industrial-sized ingots could be appropriately evaluated.

[0255] On the other hand, (2)(a) steel is evaluated using ingots of industrial size with small actual solidification rates (ingots with a mass of 8 tons or more).

[0256] [1.2. Verification experiment on the upper limit of C]

[0257] [1.2.1. Sample Preparation]

[0258] [A. Making a round rod]

[0259] The following verification shows the reduction in impact value when the C content exceeds 0.31% by mass.

[0260] The steel composition (mass %) was set as 1.20Si-0.06Cu-0.11Ni-1.31Mn-5.89Cr-1.68Mo-0.019Al-0.027N-0.18V, with the carbon content systematically varied. These steel grades were cast into 150kg ingots. After ingot manufacturing, homogenization heat treatment, hot working, normalizing, and tempering were performed.

[0261] It should be noted that normalizing and tempering were performed in this verification, but these processes can be omitted. Additionally, although not performed in this verification, spheroidizing annealing (SA) is sometimes performed after hot working or tempering. Through the above processes, tempered steel bars (round bars) with a diameter of approximately 82 mm and a length of approximately 3000 mm were manufactured.

[0262] [B. Heat treatment of square bars simulating hot working]

[0263] Ten square bars, each 12mm × 12mm × 55mm, were made from the tempered round bars.

[0264] The resulting square bars were heated to reproduce the austenite grain size during industrial heat treatment. Specifically, they were held at 1240°C for 2 hours in a vacuum. In industrial processes, heat treatment is not necessarily performed in a vacuum, but since simulating the temperature history was for verification purposes, heat treatment was carried out in a vacuum.

[0265] Next, the square bar was subjected to a heat treatment simulating the cooling process after hot working of the ingot into large-sized steel. Specifically, it was held at 1240°C for 2 hours, then cooled to 1000°C at a rate of 1°C / min, and then cooled from 1000°C to 600°C at a rate of 0.5°C / min.

[0266] It should be noted that, depending on the composition, carbides or carbonitrides may sometimes precipitate in a dotted pattern at the austenite grain boundaries within this temperature range.

[0267] In the temperature range below 600℃, inert gas is introduced into the vacuum furnace and pressurized to 3-4 Torr (0.40-0.53 kPa) to further force the inert gas to convect, thereby rapidly cooling the square rod.

[0268] Cooling rates below 600°C cannot simulate the characteristics of large-sized steel products manufactured industrially. However, since the purpose of this evaluation is to investigate the "effect of grain boundary carbides precipitated at grain boundaries in the high-temperature region after hot working," the objective can be achieved even with a cooling history below 600°C as described above. Grain boundary carbides do not disappear even during the "normalizing-tempering-quenching-tempering" process after hot working and will eventually remain in the mold, thus significantly reducing the impact value.

[0269] [C. Normalizing, tempering, and quenching and tempering of square bars]

[0270] Next, in a vacuum, the square bars that had undergone simulated heat treatment were normalized and tempered according to industrial methods.

[0271] Furthermore, the tempered square bar is subjected to vacuum quenching. That is, the square bar is held at 920°C for 1 hour in a vacuum. Then, inert gas is introduced into the vacuum furnace and pressurized to 3-4 Torr (0.40-0.53 kPa). The square bar is further cooled to below 200°C by forced convection of the inert gas.

[0272] The cooling time from 920°C to 200°C during quenching is less than 60 minutes. That is, the cooling of square bars differs from the cooling of large-sized steel products manufactured industrially. However, the purpose of this evaluation is to investigate "the effect of grain boundary carbides precipitated at grain boundaries in the high-temperature region after hot working," so this objective can be achieved even if the quenching is rapid cooling.

[0273] Next, the quenched square bars are further tempered. Tempering is performed by holding at 560–600°C for 2 hours and then cooling to below 200°C.

[0274] Furthermore, tempering was added. Specifically, the square bars were held at 560–600°C for a predetermined time, and then cooled to below 200°C. This treatment was performed more than once, tempering the angle bars to 39.5–40.5 HRC. The holding temperature, time, and number of treatments varied depending on the steel grade (carbon content). This is because the softening resistance differs with different carbon content.

[0275] [1.2.2. Test Methods]

[0276] Impact test specimens were fabricated from square bars tempered to 39.5–40.5 HRC. The shape of the impact test specimens was set according to JIS Z2242:2018 (10 mm × 10 mm × 50 mm, radius of curvature at the notch tip: 1 mm, notch depth: 2 mm, cross-sectional area of ​​the specimen below the notch: 0.8 cm²). 2 The obtained impact test pieces were used to conduct impact tests at 15–35°C.

[0277] The evaluation used impact values. The impact values ​​referred to here [J / cm²] 2 The absorbed energy [J] is divided by the cross-sectional area of ​​the bottom of the notch in the test piece, which is 0.8 cm². 2 The value obtained refers to the average value of 10 test pieces.

[0278] [1.2.3. Results]

[0279] The required impact value for die-casting molds is 20 J / cm² in molds with low loads. 2 The above is 25 J / cm in molds with high loads. 2 That's all. Additionally, the impact value is 30 J / cm². 2 The risk of damage is significantly reduced in the above die-casting molds.

[0280] In this evaluation, quenching was described as rapid cooling. However, in actual large molds, where quenching is slow cooling, the impact value decreases by 5 J / cm. 2 Approximately. Therefore, the threshold for the impact value used to determine whether it is good or bad is set to 25 J / cm. 2 .

[0281] Figure 1 The relationship between carbon content and impact value is shown. The impact test specimens used in the tests differ from the large molds; they are quenched by rapid cooling. Nevertheless, when carbon content is excessive, the impact value is less than 20 J / cm². 2 The test pieces. This shows that the influence of grain boundary carbides precipitated in the high-temperature region after heat processing is very significant. From Figure 1 It can be determined that the impact value is 25 J / cm. 2 The above are steel grades with a carbon content of less than 0.31% by mass.

[0282] [1.3. Verification Experiment of the Upper Limit Value of V]

[0283] [1.3.1. Making the square bar]

[0284] The following verification demonstrates the reduction in impact value when the V content exceeds 0.180% by mass.

[0285] The steel composition (mass %) was set as 0.31C-1.36Si-0.04Cu-0.13Ni-1.22Mn-5.96Cr-1.38Mo-0.018Al-0.032N, with the V content systematically varied. These steel grades were cast into 150kg ingots. Ten square bars were then produced in the same manner as the C content verification test.

[0286] [1.3.2. Test Methods]

[0287] The impact value was measured in the same manner as the verification test for C.

[0288] [1.3.3. Results]

[0289] Figure 2 The relationship between V quantity and impact value is shown. The impact test specimens used in the tests differ from the large molds; they are quenched by rapid cooling. Nevertheless, when V quantity is excessive, the impact value is less than 20 J / cm². 2The test pieces. This shows that the influence of grain boundary carbides precipitated in the high-temperature region after heat processing is very significant. From Figure 2 It can be determined that the impact value is 25 J / cm. 2 The above are steel grades with a V content of less than 0.180% by mass.

[0290] [1.3.4. Preferred ranges for C and V quantities]

[0291] Figure 3 The ranges for carbon (C) and volume (V) are shown. In this invention, the C and V values ​​are defined considering "hardness," "the amount of coarse foreign matter," "the amount of grain boundary carbides precipitated at grain boundaries after hot working," and "the amount of pinned particles." Conventional hot die steels have a C value of 0.32% by mass or more and a V value of 0.30% by mass or more. In contrast, the steel involved in this invention has a C value of 0.31% by mass or less and a V value of 0.180% by mass or less; therefore, the ranges for C and V values ​​differ from those of conventional steels.

[0292] Furthermore, the quenching temperature of this invention differs from that of existing steels. To ensure sufficient solid solution formation of C and V, existing steels are quenched at high temperatures of 1010–1040°C. In contrast, the quenching temperature of this invention, with its lower C and V content, can be as low as 880–980°C.

[0293] Therefore, the steel involved in this invention has the following advantages: (a) it can reduce CO2 emissions, (b) the steel after quenching has small deformation and is less prone to cracking.

[0294] [1.4. Verification Tests for Mn and Cr Contents]

[0295] [1.4.1. Sample Preparation]

[0296] The effects of Mn and Cr content on hardenability and impact value were verified below.

[0297] The steel composition (mass %) was set as 0.25C-0.81Si-0.08Cu-0.09Ni-1.78Mo-0.05V-0.028Al-0.011N, with the Mn and Cr contents systematically varied. These steel grades were cast into 150kg ingots. Following the same procedure as the C content verification test, ten 12mm×12mm×55mm square bars and one 12mm×12mm×20mm small piece were fabricated.

[0298] The aforementioned square bars and small pieces were quenched in a vacuum at 920°C for 1 hour. The cooling rate during quenching was set to 8°C / min from 920°C to 750°C, 5°C / min from 750°C to 500°C, and 0.5°C / min from 500°C to 200°C. There was no special control over the cooling rate from 200°C to below 100°C.

[0299] The above quenching process is an example of an internal process with the minimum cooling rate when quenching large steel pieces weighing over 3000 kg. The phase transformation is essentially complete when the temperature reaches 200°C, therefore there is no particular control over the cooling rate from there down to below 100°C.

[0300] Next, the square rods and small pieces were tempered. Tempering was performed by holding at 560°C for 2 hours and then cooling to below 200°C.

[0301] Furthermore, tempering was added. Specifically, the aforementioned square bars and small pieces were held at 560–600°C for a predetermined time, and then cooled to below 200°C. This treatment was performed more than once, tempering the square bars and small pieces to 39.5–40.5 HRC. The holding temperature and time, as well as the number of treatments, varied depending on the steel grade (Mn and Cr content). This is because the softening resistance differs when the Mn and / or Cr content is different.

[0302] [1.4.2. Test Methods]

[0303] [A. Impact Test]

[0304] Impact test specimens were fabricated from square bars tempered to 39.5–40.5 HRC. The shape of the impact test specimens was set according to JIS Z2242:2018 (10 mm × 10 mm × 50 mm, radius of curvature at the notch tip: 1 mm, notch depth: 2 mm, cross-sectional area of ​​the specimen below the notch: 0.8 cm²). 2 The obtained impact test pieces were used to conduct impact tests at 15–35°C.

[0305] The evaluation used impact values. The impact values ​​referred to here [J / cm²] 2 The absorbed energy [J] is divided by the cross-sectional area of ​​the bottom of the notch in the test piece, which is 0.8 cm². 2 The value obtained refers to the average value of 10 test pieces.

[0306] [B. Resistance to softening]

[0307] The softening resistance was evaluated using small pieces tempered to 39.5–40.5 HRC. The tempered pieces were held at 560°C for 24 hours and then cooled to room temperature. The HRC hardness was then measured at room temperature.

[0308] [1.4.3. Results]

[0309] [A. Impact Test]

[0310] Figure 4 This illustrates the effect of Mn and Cr content on impact values ​​at low quenching rates. Figure 4 In the diagram, "×" indicates that the impact value is less than 25 J / cm. 2 "○" indicates an impact value of 25 J / cm 2 Above and below 30 J / cm 2 "●" indicates an impact value of 30 J / cm 2 The solid line represents the correlation line when Mn / Cr = 0.150, and the dashed line represents the correlation line when Cr = 5.60% by mass. Additionally, a single-dotted line represents the correlation line when Mn + Cr = 6.60% by mass, and a double-dotted line represents the correlation line when Mn + Cr = 6.80% by mass.

[0311] according to Figure 4 It can be seen that (a) when Mn / Cr > 0.15 and Cr ≥ 5.60% by mass, the impact value is 25 J / cm. 2 The above; (b) when Mn+Cr≥6.60 wt%, the impact value becomes higher; and (c) when Mn+Cr≥6.80 wt%, the impact value becomes even more stable at a high level.

[0312] Based on the above, it can be confirmed that the steel involved in this invention has high hardenability under conditions where the influence of coarse foreign matter and grain boundary carbides is minimal.

[0313] [B. Resistance to softening]

[0314] Figure 5 The effect of Cr on softening resistance is shown. The less the decrease in hardness after heat treatment relative to the initial hardness of 40 HRC, the higher the softening resistance. According to... Figure 5 It can be seen that when the Cr content exceeds 6.60% by mass, the resistance to softening deteriorates significantly.

[0315] [1.4.4. Preferred ranges for Mn and Cr content]

[0316] The preferred ranges for Mn and Cr content were determined based on the above. Figure 6 The ranges for Mn and Cr amounts are shown. Figure 6 The area enclosed by the four lines is the range of steel materials involved in this invention.

[0317] The existing range for Mn and Cr content in hot die steels is Mn < 0.80% by mass and Cr < 5.80% by mass. This range is outside the range of... Figure 6 The area to the lower left of the range shown. According to Figure 6 and Figure 3It is known that the composition of the steel involved in this invention is completely different from that of traditional hot die steel.

[0318] [1.5. Verification Experiment of the Lower Limit of Si Content]

[0319] [1.5.1. Preparation of the test piece]

[0320] The following section verifies the effect of Si content on machinability.

[0321] The steel composition (mass%) was set as 0.22C-1.09Mn-0.07Cu-0.18Ni-6.12Cr-1.01Mo-0.04V-0.023Al-0.016N, with the Si content systematically varied. These steel grades were cast into 150kg ingots. Following the same verification test for the C content, tempered steel bars (round bars) with a diameter of approximately 82mm and a length of approximately 3000mm were produced.

[0322] Next, blocks of 50mm × 25mm × 200mm were cut from the tempered round bar. Then, the blocks were quenched and tempered under the same conditions as the verification tests for Mn and Cr content, and the blocks were tempered to 39.5–40.5 HRC.

[0323] [1.5.2. Test Methods]

[0324] The wear of the cutting tool was measured using a cutting block. The cutting distance at which the wear reached 300 μm was defined as the tool life. A longer cutting distance was considered to indicate better machinability.

[0325] [1.5.3. Results]

[0326] Figure 7 This illustrates the effect of Si content on machinability. With low Si content, machinability is poor, and machining time becomes excessive. This is particularly true in large molds where the cutting volume is high, making industrially feasible when machinability deteriorates. According to... Figure 7 It is known that when the Si content is 0.40% by mass or higher, the machinability improves dramatically. Furthermore, it is known that when the Si content is 0.60% by mass or higher, machinability close to that of SKD61, which is rated as having "very good machinability," can be obtained. Additionally, it is known that even with further increases in the Si content, the machinability approaches saturation.

[0327] [1.6. Verification Experiment of Lower and Upper Limits of Mo Quantity]

[0328] [1.6.1. Preparation of the test piece]

[0329] The following section verifies the effect of Mo content on softening.

[0330] The steel composition (mass%) was set as 0.29C-0.70Si-1.39Mn-0.07Cu-0.12Ni-5.79Cr-0.03V-0.026Al-0.010N, with the Mo content systematically varied. These steel grades were cast into 150kg ingots. Following the same verification test for the C content, tempered steel bars (round bars) with a diameter of approximately 82mm and a length of approximately 3000mm were produced.

[0331] Next, small pieces of 12mm×12mm×20mm were cut from the tempered round bar. Then, the small pieces were quenched and tempered under the same conditions as the verification test for Mn and Cr content, and the small pieces were tempered to 39.5~40.5HRC.

[0332] [1.6.2. Test Methods]

[0333] The softening resistance was evaluated using small pieces tempered to 39.5–40.5 HRC. The tempered pieces were held at 560°C for 24 hours and then cooled to room temperature. The HRC hardness was then measured at room temperature.

[0334] [1.6.3. Results]

[0335] Figure 8 The effect of Mo on softening resistance is shown. Both insufficient and excessive Mo concentrations reduce softening resistance. Molds manufactured through the PH process generally have a hardness above 35 HRC. According to... Figure 8 It can be seen that in order to ensure a hardness of 35 HRC or higher after heat treatment at 560℃ for 24 hours, it is sufficient to set the Mo content to 0.60% by mass or more and 2.00% by mass or less.

[0336] [2. Verification test using large ingots]

[0337] [2.1. Summary]

[0338] In the verification test of the preferred element amounts, a small-sized (150 kg) ingot was used to manufacture steel with a small cross-section. Test pieces made from this steel were subjected to heat treatment simulating industrial manufacturing methods (steel for large molds and the manufacturing method of large molds). Thus, the properties of this steel "other than 2(a)" when manufactured by industrial methods and used as molds can be appropriately evaluated.

[0339] On the other hand, in the following embodiments, the effects of the present invention were confirmed by actually using ingots with a mass of 8 tons or more. In this case, the steel was quenched and tempered to verify the internal impact value. That is, "2(a)" above was verified. This is because other properties have already been verified in the verification test of the preferred element amounts.

[0340] [2.2. Sample Preparation]

[0341] [2.2.1. Block Fabrication]

[0342] Table 1 shows the composition of the steels whose properties were verified (Examples 1-13, Comparative Examples 1-3). Comparative Example 1 is equivalent to JIS SKD6 (AISI H11). Comparative Example 2 is equivalent to a commercially available steel with Si-Mn-Cr modified SKD6, which is a steel with superior hardenability and resistance to thermal cracking compared to SKD6. Comparative Example 3 is a steel with C and V contents exceeding the upper limits of the present invention. It should be noted that although not listed in Table 1, all steels contain impurity elements such as P within the range not exceeding the above-mentioned upper limits.

[0343] [Table 1]

[0344]

[0345] These steels were cast into ingots with a mass of approximately 21 tons. The solidification rate of a 21-ton ingot is slower than that of a 10-ton ingot, therefore large foreign objects can easily affect the impact value. Under these harsh conditions, the appropriateness of the C and V quantities was verified.

[0346] The 21-ton ingot was subjected to a high-temperature and long-duration homogenization heat treatment, followed by hot working, ultimately yielding a block measuring 740mm × 1060mm × 2440mm (approximately 15 tons). The mass difference between the ingot and the block (approximately 6 tons) is due to the mass of the portion removed due to quality and shape issues.

[0347] Regarding the heat treatment of the above-mentioned bulk materials, appropriate conditions were set according to the steel grade. Examples 1-13 were quenched starting at 920°C and tempered at 560°C-600°C. Comparative Examples 1-3 were quenched starting at 1030°C and tempered at 580-630°C after normalizing, tempering, and spheroidizing annealing. In this way, the surface hardness of all 16 steel grades was set to a pH state of approximately 40 HRC.

[0348] [2.2.2. Production of Material 2 and Material 3]

[0349] Areas with more large foreign objects are located near the center where the solidification rate is low. Therefore, such as Figure 9As shown, a first material 12 is cut from near the center of the c-axis of block 10 (a = 740 mm, b = 1060 mm, c = 2440 mm, w ≒ 15000 kg). Next, a second material 14 is cut from approximately the center of the ab-plane of the first material 12, and a third material 16 is cut from the end of the first material 12. It should be noted that in this experiment, d = 35 mm, e = 95 mm, f = 135 mm, and g = 50 mm are used.

[0350] [2.3. Test Methods]

[0351] [2.3.1. Hardness]

[0352] Small pieces measuring 15mm × 15mm × 35mm were cut from the corners of material 14 (95mm × 135mm × 35mm). Additionally, small pieces measuring 15mm × 15mm × 35mm were cut from near the center of material 16 (50mm × 50mm × 35mm). These small pieces were ground and polished to adjust for parallelism and surface roughness suitable for hardness measurement. Using these small pieces, Rockwell C scale hardness (hardness H1 at the periphery, hardness H2 at the center) was measured at room temperature.

[0353] [2.3.2. Impact Test]

[0354] Twenty impact test pieces, each measuring 10mm × 10mm × 55mm, were fabricated from material 14 (95mm × 135mm × 35mm). Impact tests were then conducted on these test pieces at temperatures ranging from 15 to 35°C.

[0355] [2.4. Results]

[0356] [2.4.1. Hardness]

[0357] Table 2 shows ΔH, H1, and H2. In Examples 1-13 and Comparative Example 3, the hardness H1 of the outer periphery of the block was 36.7-42.8 HRC, and the hardness H2 of the center was 38.8-43.7 HRC. Furthermore, the absolute value of the difference between H1 and H2, ΔH (hardness homogeneity), was 0.5-3.4 HRC. That is, it is confirmed once again that when Mn / Cr > 0.150 and Cr ≥ 5.60% by mass, high hardenability and high hardness homogeneity are observed. Due to the small ΔH, the characteristic difference between the outer periphery and the center of the steel is also small, and it can be expected that the mold performance made from any part of the steel will be highly stable.

[0358] In Comparative Examples 1 and 2, the hardness H1 of the outer periphery of the block was 41.2 and 41.8 HRC, respectively. Furthermore, the hardness H2 of the center was 45.3 and 45.5 HRC, respectively. Additionally, ΔH was approximately 4 HRC.

[0359] That is, in Comparative Examples 1 and 2, Mn / Cr ≤ 0.150 and Cr ≤ 5.60% by mass, resulting in poorer hardenability and hardness homogeneity. Due to the large ΔH, the characteristics of the outer periphery and the center of the steel differ greatly, and the performance of the mold may vary significantly depending on which part of the steel it is made from.

[0360] [2.5.2. Impact Test]

[0361] Table 2 shows the average impact value, less than 20 [J / cm]. 2 The number of [items] and the low impact value rate. The average impact value of Examples 1-13 is 30 [J / cm]. 2 The impact values ​​are above 20 [J / cm²], and the low impact value rate is below 30%. Examples 1-13, in addition to high hardenability, have low C and V content, resulting in fewer coarse foreign matter or dotted carbides or carbonitrides. As a result, even when slowly quenching materials cut from near the center of a large profile material with a low solidification rate, the impact value remains high and stable. However, because there are no coarse foreign matter from C or V, and there are also foreign matter without C or V, the impact value is less than 20 [J / cm²]. 2 The test piece also occurred with a low probability.

[0362] On the other hand, the average impact value of Comparative Examples 1 to 3 is less than 30 [J / cm]. 2 The low impact value rate exceeded 30%. In addition to low hardenability, Comparative Examples 1-3 had higher C and V content, resulting in more coarse foreign matter or dotted carbides or carbonitrides. As a result, when material cut from near the center of a large section of material with a low solidification rate was slowly quenched, the impact value became lower.

[0363] Comparative Example 3 is a steel with increased C and V content compared to Examples 1-13. Therefore, Comparative Example 3 has high hardenability, but contains more coarse foreign matter or dotted carbides or carbonitrides. As a result, the impact value of Comparative Example 3 is lower than that of Examples 1-13. That is, in the case of large-section materials, hardenability alone cannot be used to evaluate the impact value, and the importance of reducing C and V content can be confirmed.

[0364] Based on the results in Table 2, it can be determined that the impact value of large molds (weighing over 2000 kg) manufactured from steels of Examples 1 to 13 through the PH process is also higher than that of molds manufactured from existing steels with higher C or V content.

[0365] [Table 2]

[0366]

[0367] [3. Universality]

[0368] The above describes the conception and verification of a die-casting mold. However, this invention is not limited to die casting and can be applied to molds or parts used in various casting processes. Furthermore, in addition to casting, it is also applicable to molds or parts used in forging, hot stamping, extrusion, resin injection molding, resin blow molding, and the molding or processing of rubber or fiber-reinforced plastics.

[0369] In addition, in the above verification, the steel was quenched from 920°C and tempered at 560-600°C to about 40 HRC to evaluate the properties. However, depending on the wide range of quenching temperatures and applications, steel that can be tempered to a wide range of hardness at a wide range of tempering temperatures can be used in molds or parts.

[0370] In the verification of properties, molten blocks were used, but the steel involved in this invention can also be used in the form of powder, bars, wires or plates.

[0371] For example, if the steel involved in this invention is made into powder, it can be applied to various successive molding processes such as stacked molding (SLM, LMD, etc.) or PPW.

[0372] Furthermore, if the steel involved in this invention is used as a molten bar, it can also be used to manufacture molds or components. Alternatively, if the steel involved in this invention is used as a molten bar or wire, it can be applied to laminated shapes or repairs using TIG welding or laser welding.

[0373] Furthermore, if the steel involved in this invention is used as a sheet material, it can also be joined together to manufacture molds or components. Of course, molds or components can also be manufactured by joining parts made of the steel involved in this invention.

[0374] As described above, the steel of the present invention can be applied to components having various shapes. Furthermore, molds or parts, or repairs, can be manufactured using various methods based on the various shapes of materials made from the steel of the present invention.

[0375] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to any of the above embodiments, and various changes can be made without departing from the spirit of the present invention.

[0376] This application is based on Japanese Patent Application 2022-167688, filed on October 19, 2022, the contents of which are incorporated herein by reference.

[0377] Industrial applicability

[0378] The steel involved in this invention can be used as molds or components thereof in various processes such as casting, forging, hot stamping, extrusion, injection molding, and blow molding.

Claims

1. A steel material, comprising: 0.21≤C≤0.31 mass%, 0.013≤V≤0.180 mass%, 0.896≤Mn≤1.50 mass%, 5.60≤Cr≤6.60 mass%, Cu+Ni≤0.84 mass%, 0.40≤Si≤1.40 mass%, 0.60≤Mo≤2.00 mass%, 0.001≤Al≤0.080 mass%, and 0.003≤N≤0.040 mass%, with the balance being Fe and unavoidable impurities, and the contents of Mn and Cr satisfy Mn / Cr≥0.160 and Mn+Cr≥6.60 mass%.

2. The steel material according to claim 1, further comprising one or more groups selected from the following groups A to D: Group A: one or two selected from 0.30<W≤2.00 mass% and 0.30<Co≤1.00 mass%; Group B: 0.0002<B≤0.0080 mass%; Group C: one or more selected from the following: 0.006<S≤0.180 mass%, 0.0005<Ca≤0.0500 mass%, 0.03<Se≤0.50 mass%, 0.005<Te≤0.100 mass%, 0.01<Bi≤0.50 mass%, and 0.03<Pb≤0.50 mass%; Group D: one or more selected from the following: 0.004<Nb≤0.100 mass%, 0.004<Ta≤0.100 mass%, 0.004<Ti≤0.100 mass%, and 0.004<Zr≤0.100 mass%.

3. The steel material according to claim 1, having a mass of 3000 kg or more, Among the vertical dimension L1, the horizontal dimension L2, and the vertical dimension L3, the smallest dimension L is... min It is 300mm or more.

4. The steel material according to claim 1, wherein, the hardness at the central part is 35 HRC or more and 45 HRC or less.

5. The steel material according to claim 1, wherein, the absolute value of the difference between the hardness at the central part and the hardness at the outer peripheral part is 3.5 HRC or less.

6. The steel material according to claim 1, wherein, The average impact value is 25 J / cm. 2 above.

7. The steel material according to claim 1, wherein, the low impact value ratio is 30% or less, The low impact value rate refers to an impact value of less than 20 J / cm. 2 The ratio of the number of impact test pieces n to the total number of impact test pieces n0 that underwent impact testing is n × 100% / n0.

8. A die, which is manufactured from the steel material according to any one of claims 1 to 7, and has a mass of 2000 kg or more.

Citation Information

Patent Citations

  • Tool steel for hot work and steel product using the same

    JP2011001572A

  • Processing device and control method therefor

    JP2022167688A

  • Die steel superior in spheroidizing annealing property and hardenability

    JP2008121032A